PENGARUH ASSETS TERHADAP RENTABILITAS PADA PT. INDAH KIAT PULP &PAPER DI KECAMATAN PERAWANG - Bangkit Suryadi Rajagukguk; Makhdalena Makhdalena; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to look at the effect of assets on rentability. The analysis unit of this study is PT. Beautiful Tips Pulp & Paper. The type of data used from this study is secondary data derived from IDX. The data analysis techniques used are descriptive and quantitative (simple regression) with the help of SPSS. The results showed that assets affected rentability by 53.4% and the remaining 46.6% was influenced by other variables that were not studied in this study such as sales, debt, TOA and TOI.Key Words : Assets, Rentability,